If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 9y + -8(6x + -4y) = 0 8x + 9y + (6x * -8 + -4y * -8) = 0 8x + 9y + (-48x + 32y) = 0 Reorder the terms: 8x + -48x + 9y + 32y = 0 Combine like terms: 8x + -48x = -40x -40x + 9y + 32y = 0 Combine like terms: 9y + 32y = 41y -40x + 41y = 0 Solving -40x + 41y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-41y' to each side of the equation. -40x + 41y + -41y = 0 + -41y Combine like terms: 41y + -41y = 0 -40x + 0 = 0 + -41y -40x = 0 + -41y Remove the zero: -40x = -41y Divide each side by '-40'. x = 1.025y Simplifying x = 1.025y
| -(32m+74n+3)= | | 4.7*-2.3= | | -(z+18)= | | 15u+12+20u+40= | | 3x^2=8-7x | | 4a^2+12a+9=144 | | 998+9= | | 3x-x= | | 17d-12d= | | -4X+5Y=33 | | -5.05*-2= | | -(2x+4)-(x-5)= | | 10-5m=20 | | 3x^2-12x+3=x^2-4 | | -3/4*(-6/7)= | | 8*-6= | | 2(x+3)-(3x-5)= | | x^6-152x^3+3375=0 | | 12x-9/3= | | 8x-4(6x+1)= | | 16x^2-16x+2.56=0 | | 8a-14b= | | 4x+2(3x-2)= | | 3x-6y=8 | | 8+2x-5-3x= | | 2m+24= | | 36-19x=-6x+41 | | -5(-9a-8b+2)= | | 3-3y^2=0 | | -9(n-1)= | | 3(m-2)= | | -3/2*5= |